Theoretical background for increasing grip properties of wheeled tractors based on their rational ballasting - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Nadykto, Volodymyr; Надикто, Володимир Трохимович; Надыкто, Владимир Трофимович; Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Nesvidomin, Viktor; Ivanovs, Semjons; Olt, Jüri (My University, 2019)
The correct selection of the level of mechanical ballasting for wheeled tractors is among the most important issues for increasing their utilisation efficiency, in particular, increasing their grip properties. The shortcoming of the earlier undertaken investigations was that they virtually did not take into account the allowed maximum pressure of the tractor’s wheels on the soil. At the same time, little attention was paid to the impact of the maximum load-carrying capacity of the wheel tyres. The aim of the paper is to eliminate these deficiencies. Because of the authors’ efforts, the new technique has been developed, which differs in that it employs the requirement of the tyre’s ecofilic properties. The implementation of this requirement implies setting the maximum allowed level of the tractor wheels’ pressure on the soil and taking into account the maximum load-carrying capacity of the wheel tyres as well as the vertically applied load on each of the tractor’s axes under the simultaneous action of both the horizontal and vertical components of the tractive resistance of the employed agricultural implement. The practical effectiveness of the new approach is shown by the example of determining the possibility and level of ballasting the specific wheeled tractor operating as part of a ploughing unit
Keywords: tractor; ballast; wheel load; ire